Customer Relationship Management in Industrial Bank - Kumar, Dileep (Information Management and Business Review, 2013)
Banking sector is in the midst of acute competion at national and international level. The way banks entertain and maintain their customers that determins its future business opportunities and development. Inorder to maintain the customers, employees working in banking sector need to be well equipeed with adequate skills in relationship marketing. A case study has been conducted in one of the Malaysian Bank* (name changed) inorder to asertain the significance of Customer Relationship Management. Lessons about the importance of employees’ in the the implementation of Customer Relationship Management (CRM) is well established though this case study. This case study is an eye opener to the management and leaders of banking sector, inorder to have effective empoloyee engagement and development.